Implementation Of Public Health Program Model To Manage Malnutrition Among Under-Five Children In Purworejo District, Central Java - Risnawati, Risnawati; Susilowati, Tuti; Apreliasari, Helmy (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2024)
Background:Purworejo District in Indonesia has a persistent issue of high malnutrition rates among children under five years old. Despite efforts, the prevalence of malnutrition in this demographic continues to rise, highlighting the urgent need for effective health interventions.Aim:This study aimed to develop and evaluate the "Implementation of Public Health Program Model to Manage Malnutrition among Under-five Children in Purworejo District, Central Java". The study utilized both qualitative and quantitative research designs, incorporating descriptive and analytical methods. The research spanned from understanding health issues through program evaluation, conducted in Grantung Village, Bayan Sub-District, Purworejo District, from August to November 2023.Method:The study employed a mixed-methods approach, beginning with advanced identification of health issues, followed by model creation, implementation of the health program, community education, and evaluation of the "Implementation of Public Health Program Model to Manage Malnutrition among Under-five Children in Purworejo District, Central Java”. Ethical approval was obtained from the Health Research Ethics Commission of Semarang State University and research permission from the Purworejo District Government. Participants provided informed consent before taking part in the study.Result:The study found that the implemented public health program model effectively addressed malnutrition among under-five children in Purworejo District. Significant improvements were observed in the knowledge (p-value=0.001), attitude (p-value=0.001), and perception (p-value=0.023) of parents/caretakers regarding malnutrition.Conclusion:The "Implementation of Public Health Program Model to Manage Malnutrition among Under-five Children in Purworejo District, Central Java” demonstrated its efficacy in indirectly managing malnutrition among children in the region. The findings underscore the importance of tailored health interventions in addressing community health challenges like malnutrition effectively.